Effect of direct oral anticoagulants in patients with atrial fibrillation with mitral or aortic stenosis: A review - Guo, Guigao; Liang, Shucheng; Guan, Zeyu; Zhu, Ke (Frontiers in Cardiovascular Medicine, 2022)
Background: Several studies summarized the clinical performance of direct oral anticoagulants (DOACs) in atrial fibrillation (AF) patients with mitral stenosis or aortic stenosis. The significance of this systematic review was to provide clinicians and scientists the latest update of the clinical application of DOACs specifically in managing this specific population. Methods: Literatures from the PubMed database up to July 2022 were screened for inclusion. Studies on the effect of DOACs in patients suffering from AF with mitral or aortic stenosis were assessed for further selection. Results: Results from four studies were gathered and discussed: the RISE MS trial, DAVID-MS study, and two observational studies by Melgaard et al, and Kim et al. In the Korean observational study with a 27-months mean follow-up duration and a sample population consisted of patients with mitral stenosis and AF, the thromboembolic events happened at a rate of 2.22%/ year in the DOAC group and 4.19%/year in the warfarin group (adjusted hazard ratio: 0.28; 95% CI: 0.18-0.45). Intracranial hemorrhage occurred at rates of 0.49% and 0.93% in the DOACs and the warfarin groups, respectively (adjusted hazard ratio: 0.53; 95% CI: 0.22-1.26). In the Danish observational study, which had a sample pool with AF patients with aortic stenosis, reported that the adjusted hazard ratios for thromboembolism and major bleeding were 1.62 (95% CI, 1.08-2.45) and 0.73 (0.59-0.91) for DOACs compared with warfarin during 3 years of follow-up. In the RISE-MS trial involving AF patients with mitral stenosis, there were no differences in ischemic stroke, systemic embolic events, or major bleeding between the rivaroxaban versus warfarin groups during a 1-year follow-up as well as equal rate of increased thrombogenicity in the left atrial appendage at 6 months. The rate of silent cerebral ischemia at 12 months was higher in the warfarin group (17.6%) than in the rivaroxaban group (13.3%). Conclusions: Current published studies supported DOACs’ effectiveness in preventing thromboembolism in patients of AF with mitral or aortic stenosis. Further clinical trials could confirm these findings.